Different Views of Domestic Violence-Suicide Attempts or Homocides - Research Paper - Ekinci, Ecesu; Tarımer, Mehmet Levent; Ersoy, Burcu; Balcı, Yasemin (The Bulletin of Legal Medicine, 2024)
Objective: It was aimed to emphasize the relationship between domestic violence and suicides by evaluating the cases referred to prepare a report due to domestic violence, suicide attempt and homicide.Methods: From 2014 until the end of 2022, cases who applied to our polyclinic due to suicide attempt and domestic violence were analyzed.Results: In 763 (69.4%) cases reported due to domestic violence, the perpetrator was the spouse/partner, and in the remaining cases, the violence came from other domestic individuals. 686 (89.9%) cases of spousal/partner violence and 180 (53.6%) of cases of nonspousal/partner domestic violence belong to women. 631 (4.2%) of the reports were due to suicide attempt, and 402 (63.7%) of them belonged to women. It was determined that 17 of the female cases who attempted suicide were reported due to violence by spouse/partner before/after the attempt, and in 19 (4.7%) of them, including domestic violence in 2 cases, by spouse/partner and other domestic individuals. In men, the number of cases in this group is 5, and the rate is 2.2%. Only 1 of them is spousal violence and the others are domestic violence. According to results obtained, the rate of suicide attempt in cases of spousal/partner violence was 2.2%, while the rate of suicide attempt was 6.8% in cases diagnosed with mental disorder due to spousal/ partner violence.Conclusion: It has been suggested that detailed evaluation of both suicide attempters and victims of domestic violence will contribute to the solution of both social problems.
Keywords: Domestic violence; Suicid; Forensic Medicine